Effect of streaming water vapor on the corrosion behavior of Ti60 alloy under a solid NaCl deposit in water vapor at 600 °C. (November 2019) - Fan, Lei; Liu, Li; Cui, Yu; Cao, Min; Yu, Zhongfen; Oguzie, Emeka E.; Li, Ying; Wang, Fuhui
Highlights: First quantitatively study H2 O involves into oxides on Ti60 alloy under NaCl at 600 °C. H2 O involves into the reaction of solid NaCl and TiO2 to form Na4 Ti5 O12 at 600 °C. H2 O promotes the crystallinity of corrosion product of Ti60 alloy under NaCl at 600 °C. Abstract: The corrosion behavior of Ti60 alloy coated with solid NaCl layer in dry O2 and humid O2 (30.8 vol.% H2 O) environments at 600 °C have been investigated. The isotopic tracing of 18 O showed involvement of H2 O in both the outer corrosion layer (OCL) and the inner corrosion layer (ICL). Theoretical calculations revealed that H2 O provided 14% and 21% of the oxygen required for the formation of the outer and inner corrosion layers, respectively. Detailed analysis of corrosion products revealed that H2 O enhanced the reaction of solid NaCl and TiO2 to form Na4 Ti5 O12 and promoted the crystallinity of corrosion products.